Hibriditas Komunikasi Politik dan Birokrasi: Analisis Program "Berani Cerdas" Gubernur Sulawesi Tengah dalam Perspektif Masyarakat dalam Jaringan - Ubaidillah; Ilyas; Herman, Achmad; Alatas, Raisa (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2026)
In the era of decentralization, the gap between populist political promises and the reality of bureaucratic implementation often hinders regional development. This study aims to analyze the political communication strategy of the Governor of Central Sulawesi, Dr. H. Anwar Hafid, M.Si., in implementing the "Berani Cerdas" free education policy innovation. Employing a qualitative approach with a constructivist-policy analysis design, this research reconstructs Dan Nimmo’s political communication theory by dialoguing it with the concept of the Network Society. Data collection was conducted through process tracing, in-depth interviews, and netnography. The findings indicate that: (1) The Governor successfully transformed from an electoral political actor into a Policy Entrepreneur by leveraging his technocratic track record as credibility capital; (2) The communication strategy employed is hybrid (omni-channel), integrating legal-formal authority, conventional mass media, and digital virality to reach cross-generational audiences; (3) The audience (students) are no longer passive message consumers but act as Network Validators who verify political promises through empirical experience. This study concludes that political communication serves not merely as a branding tool, but as a strategic instrument to enforce bureaucratic performance (bureaucratic enforcer) and mobilize public participation, effectively bridging the gap between political rhetoric and the reality of public services.